Effectiveness of Parent Training Programs for ADHD : A Systematic Review - Fitria Luluk Mukhasona; Ratu Qurroh' Ain; Yuniar Pukuk Kesuma (The International Journal of Medical Science and Health Research, 2025)
Introduction Attention-Deficit/Hyperactivity Disorder (ADHD) is a prevalent neurodevelopmental disorder that significantly impacts children's functioning and family dynamics. Parent Training (PT) is a cornerstone non-pharmacological intervention designed to equip parents with skills to manage challenging behaviors. However, effectiveness varies across different programs, delivery formats, and combinations with medication, creating a need for clear evidence synthesis. This review systematically evaluates the evidence for PT's effectiveness on child symptoms, parenting, and family dynamics. Methods Following PRISMA 2020 guidelines , a systematic search of PubMed, Google Scholar, Springer, Wiley Online Library, and Semantic Scholar was conducted. Inclusion criteria targeted randomized controlled and quasi-experimental studies published in the last decade that evaluated a structured PT program for children with ADHD. After screening over 3,000 records, 40 studies were selected for the final qualitative analysis. Results The synthesis of 40 studies revealed that PT is highly effective; 35 studies reported significant reductions in core ADHD symptoms and related disruptive behaviors. Substantial secondary benefits were also found, with 27 studies documenting improved parenting practices, reduced parental stress, and increased parental competence. Therapist-led, in-person programs demonstrated advantages in adherence and satisfaction over blended or remote formats. Furthermore, combining PT with medication, particularly using a "behavior-first" approach, was found to be superior to medication alone. Discussion The findings confirm PT as a robust, evidence-based intervention with a dual benefit for both children and their caregivers. While broadly effective, the evidence underscores that a one-size-fits-all approach is insufficient. Optimal outcomes depend on tailoring the program type and delivery format to individual family needs, resources, and circumstances to maximize engagement and positive results. Conclusion Parent Training is a fundamental component of comprehensive ADHD care that effectively reduces child symptoms while enhancing parenting skills and overall family well-being. A personalized clinical approach is recommended, prioritizing behavioral interventions as a first-line treatment to achieve durable and meaningful success.